IFC Annual Report 2015 : Private Sector Matters for Development - International Finance Corporation (Washington, DC: World Bank Group, 2015)
International Finance Corporation (IFC or the Corporation) is the larg¬est global development institution focused on the private sector in developing countries. Established in 1956, IFC is owned by 184 mem¬ber countries, a group that collectively determines its policies. IFC is a member of the World Bank Group (WBG) but is a legal entity separate and distinct from IBRD, IDA, MIGA, and ICSID, with its own Articles of Agreement, share capital, financial structure, management, and staff. Membership in IFC is open only to member countries of IBRD. IFC helps developing countries achieve sustainable growth by financ¬ing private sector investment, mobilizing capital in international financial markets, and providing advisory services to businesses and governments. IFC’s principal investment products are loans and equity investments, with smaller debt securities and guarantee port¬folios. IFC also plays an active and direct role in mobilizing additional funding from other investors and lenders through a variety of means. Such means principally comprise: loan participations, parallel loans, sales of loans, the non-IFC portion of structured finance transactions which meet core mobilization criteria, the non-IFC portion of com¬mitments in IFC’s initiatives, and the non-IFC investment portion of commitments in funds managed by IFC’s wholly owned subsidiary, IFC Asset Management Company LLC (AMC), (collectively Core Mobilization). Unlike most other development institutions, IFC does not accept host government guarantees of its exposures. IFC raises virtually all of the funds for its lending activities through the issuance of debt obligations in the international capital markets, while main¬taining a small borrowing window with IBRD. Equity investments are funded from capital (or net worth).